2023
DOI: 10.3389/fphys.2023.1086050
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo study of cardiac mechano-electric and mechano-mechanical coupling during heart development in zebrafish

Abstract: In the adult heart, acute adaptation of electrical and mechanical activity to changes in mechanical load occurs via feedback processes known as “mechano-electric coupling” and “mechano-mechanical coupling.” Whether this occurs during cardiac development is ill-defined, as acutely altering the heart’s mechanical load while measuring functional responses in traditional experimental models is difficult, as embryogenesis occurs in utero, making the heart inaccessible. These limitations can be overcome with zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…It was recently shown that acute atrial dilation in 2 dpf zebrafish by injection of a given volume into the venous circulation upstream of the heart increased the atrial stroke area, suggesting that mechano-mechanical coupling drives the adaptive increase in atrial output during development. 30 These and the present results highlight the advantage of the zebrafish model to investigate cardiac performance in vivo.…”
Section: Correlation Between Ca 2+ and Ventricular Filling With The S...supporting
confidence: 70%
See 1 more Smart Citation
“…It was recently shown that acute atrial dilation in 2 dpf zebrafish by injection of a given volume into the venous circulation upstream of the heart increased the atrial stroke area, suggesting that mechano-mechanical coupling drives the adaptive increase in atrial output during development. 30 These and the present results highlight the advantage of the zebrafish model to investigate cardiac performance in vivo.…”
Section: Correlation Between Ca 2+ and Ventricular Filling With The S...supporting
confidence: 70%
“…26 As in mammals, Ca 2+ is central in excitation-contraction coupling and largely determines force generation. 27 We have recently imaged Ca 2+ and contraction simultaneously in beating hearts of zebrafish expressing ratiometric gene-encoded Ca 2+ biosensors, 28,29 preserving the mechano-electric and mechano-mechanical coupling 30 and normal heart development. In the present study, we show the involvement of TTCCs in the conduction system of zebrafish larvae and characterize AV conduction defects induced by block of TTCCs and ERG channels.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish were then transferred to an imaging dish lined with black Sylgard (DC 170, Dow Corning, Midland, TX, USA) under a layer of 3% methylcellulose (M0387, Sigma-Aldrich, St. Louis, MO, USA) and positioned in a left-lateral-side-up orientation for an optimal view of both heart chambers. The observation dish was filled with an E3 solution containing 0.35 mM tricaine (MS-222; E10521, Sigma-Aldrich, which provides adequate anesthesia, while causing no effects on HR or cardiac mechanical function [ 40 ]) and temperature-controlled at 28 °C (TC-344C, Warner Instruments) with a warmed platform (WP-16, Warner Instruments, Hamden, CT, USA) for the duration of the experiment. Larvae were left to acclimatise for 5 min, followed by a 10 s recording of membrane voltage (V m ) or intracellular Ca 2+ dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Another approach is to use inhibitors of actin-myosin interaction like blebbistatin or its analogs [3,4]. Although these methods have allowed the investigation of electrical excitation and Ca 2+ dynamics in zebrafish [5,6], the mechano-electric and mechano-mechanic coupling mech-anisms [7], which adjust the heart rate and stroke volume to the changing physiological needs, are abrogated.…”
Section: Introductionmentioning
confidence: 99%